Tokoh Linguistik modern: M.A.K Halliday - Zahiroh, Zakiyatuz (Maliki Interdisciplinary Journal, 2026)
This article discusses the thoughts of M.A.K. Halliday as one of the most influential figures in modern linguistics through his theory of Systemic Functional Linguistics (SFL). The study aims to explain the background of Halliday’s ideas, the basic concepts of SFL, and his contribution to the development of contemporary language studies. Halliday viewed language not merely as a grammatical system, but as a form of social semiotics used by humans to construct meaning, represent experience, and establish social relationships. In this perspective, language is always closely related to the context of situation and culture. Halliday’s main concepts include the three metafunctions of language: ideational, interpersonal, and textual. He also emphasized the close relationship between text and context through the dimensions of field, tenor, and mode of discourse. This article further explains the concepts of register, code, linguistic system, and social structure as essential components of functional language analysis. The method employed is a library research approach with descriptive-analytical examination of Halliday’s works and other relevant sources. The findings indicate that SFL has strengths because it is contextual, practical, and relevant to various fields such as education, discourse analysis, media studies, and social communication. However, the theory also has limitations, particularly in its terminological complexity and challenges of cross-linguistic application. Overall, Halliday’s thought provides a strong theoretical foundation for understanding language as a dynamic and meaningful social practice.